Driving digital transformation in healthcare: a training registration system for efficiency and data-driven decision making - Mohd Affandi, Najatul Afiqah; Mohd Zahibi, Muhammad Faris Hami; Abu Bakar, Normashidayu; Hamidon, Huda; Mohd Pauzi, Nur Maizatul Ummi (Faculty of Information Management, 2025)
This paper presents the conceptual design of an Employee Training Registration Management System aimed at streamlining training workflows in healthcare. The system addresses the manual way of the hospital staff in registering training sessions. The admin will have the function to generate reports and manage submissions. Key features include user-friendly interfaces, centralized data management, rolebased access, enhancing operational efficiency, accessibility, and datadriven decision-making. The system’s paperless design also aligns with sustainability goals, reducing environmental impact. Future enhancements, such as mobile app integration and AI-powered analytics, are discussed, along with scalability potential to other departments and industries. This study highlights the system’s contribution to digital transformation, setting a precedent for modernizing workflows and improving organizational effectiveness in healthcare.